Exploring the failure factors of blockchain adopting projects: a case study of tradelens through the lens of commons theory - Najati, Issam (Frontiers in Blockchain, 2025)
Blockchain is a transformative technology with the potential to metamorphose industries, including supply chains and logistics, owing to its promise of efficiency, transparency and traceability. However, many blockchain projects have failed, requiring an analysis of the underlying reasons. This research focuses on the failure factors by studying the case of TradeLens, a supply chain platform using Blockchain to improve the visibility and coordination of international shipments. Applying Elinor Ostrom’s theory of the commons, we explored challenges related to governance, participation, interoperability, technological evolution and security. The study reveals that a lack of stakeholder engagement, unclear governance, and confidentiality concerns are major obstacles. Ostrom highlights the importance of participatory governance and a clear definition of boundaries and communities in the management of shared resources. To be successful, blockchain projects must adopt a holistic approach, with transparent governance, encourage collaboration, guarantee interoperability and invest in data security. By incorporating these recommendations and the lessons learned from past failures, future blockchain projects can improve their chances of success and make a positive contribution to the transformation of industries.